1996
DOI: 10.2737/fpl-gtr-93
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of wood preservative components and their mobility in the environment : summary of pertinent literature

Abstract: Preservative-treated wood is an economical, durable, and aesthetically pleasing building material; therefore, it is a natural choice for construction projects in our National Forests, National Parks, and other public lands. However, we need to ensure that the chemicals used in treated wood do not pose a threat to people or the environment. The purpose of this report is to provide a summary of the pertinent literature on leaching of wood preservative components and their mobility in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 49 publications
2
89
0
Order By: Relevance
“…Since the 1970s, chromated copper arsenate (CCA) has been the most common preservative used in the U.S. to treat wood intended for outdoor structures, such as playsets, decks, fences, utility poles, and marine docks (Lebow 1996;Solo-Gabriele and Townsend 1999;AWPA 2005). Recently, CCA was the subject of risk assessments by the U.S. Environmental Protection Agency (EPA) and U.S. Consumer Product Safety Commission (CPSC) for potential exposures to children who contact CCA-treated playgrounds and home decks (U.S. EPA.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, chromated copper arsenate (CCA) has been the most common preservative used in the U.S. to treat wood intended for outdoor structures, such as playsets, decks, fences, utility poles, and marine docks (Lebow 1996;Solo-Gabriele and Townsend 1999;AWPA 2005). Recently, CCA was the subject of risk assessments by the U.S. Environmental Protection Agency (EPA) and U.S. Consumer Product Safety Commission (CPSC) for potential exposures to children who contact CCA-treated playgrounds and home decks (U.S. EPA.…”
Section: Introductionmentioning
confidence: 99%
“…The relative proportions of chromium, copper, and arsenic within the samples in this study did not indicate any systematic depletion of either copper or arsenic. The proportions of chromium, copper, and arsenic in exposed CCAtreated wood can provide some indication of the extent of leaching because chromium is more leach-resistant than copper or arsenic (Lebow 1996). Sodium concentrations in all but one sample were over 1,000 ppm, and many samples contained over 10,000-ppm sodium.…”
Section: Icp-aes Resultsmentioning
confidence: 99%
“…Another issue associated with preservative-treated wood is possible leaching of preservative components from wood in service [21][22][23]. We also studied effect of coatings in reducing leaching of heavy metals (As, Cr and Cu) and found that application of one coat of semitransparent stain could effectively reduce the leaching of these preservative components on average by 60% [24].…”
Section: Effects Of Wood Treatmentsmentioning
confidence: 99%